Rapport d'activite des essais villageois: campagne 1983 - Soumare, S. (CIPEA, 1984)
Analyzes village trials conducted at Dalonguebougou in Mali in 1983 on the supplementary feeding of work-oxen and on cowpea agronomy, discussing results on weight gain, yield improvement, work output and the economics of supplementary feeding.